1996
DOI: 10.1126/science.273.5281.1564
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Representation of Hand Movements After Parietal Cortex Damage

Abstract: Recent neuroimagery findings showed that the patterns of cerebral activation during the mental rehearsal of a motor act are similar to those produced by its actual execution. This concurs with the notion that part of the distributed neural activity taking place during movement involves internal simulations, but it is not yet clear what specific contribution the different brain areas involved bring to this process. Here, patients with lesions restricted to the parietal cortex were found to be impaired selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
501
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(558 citation statements)
references
References 26 publications
49
501
1
7
Order By: Relevance
“…These were the Mini-Mental State Examination Test (MMSE), the Frenchay arm test, the Stroke Impact Scale (SIS, version 3.0), and three (partly) self-designed tests. Two of these three tests assessed patients' abilities to imagine motor acts and were based on the methods described in Sirigu et al (1996). The first test mainly assessed visual imagery abilities and asked patients to imagine their own hand in a specific position (e.g.…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…These were the Mini-Mental State Examination Test (MMSE), the Frenchay arm test, the Stroke Impact Scale (SIS, version 3.0), and three (partly) self-designed tests. Two of these three tests assessed patients' abilities to imagine motor acts and were based on the methods described in Sirigu et al (1996). The first test mainly assessed visual imagery abilities and asked patients to imagine their own hand in a specific position (e.g.…”
Section: Questionnairesmentioning
confidence: 99%
“…As the movements were quite short, for a single run participants were asked to repeat each movement five times in immediate succession. The time taken for each run was taken, with the assumption that the more complex movements take longer to imagine and execute (Decety and Jeannerod, 1995;Sirigu et al, 1996). Patients performed three runs of each condition (left/right imagery, execution), and the average of the three runs was used for analysis.…”
Section: Questionnairesmentioning
confidence: 99%
“…These regions have been involved in a number of studies in motor imagery (see reviews from Grèzes and Decety, 2001;Munzert et al, 2009). Several studies using neuroimaging (Kosslyn et al, 2001), transcranial magnetic stimulation (Ganis et al, 2000), or clinical investigations (Sirigu et al, 1996) showed that motor imagery shares neural mechanisms with movement planning (Decety et al, 1989) and movement execution (Gerardin et al, 2000;Parsons et al, 1995), in particular in premotor cortex (e.g. Ionta et al, 2010) and parietal cortex (e.g.…”
Section: Shared Spectral and Anatomical Mechanisms Between Motor Imagmentioning
confidence: 99%
“…Kosslyn, Digirolamo, Thompson, & Alpert, 1998;Parsons, 1987) and timing (e.g. Choudhury, 2007;Sirigu, et al, 1996) constraints as actual movement in healthy individuals. These findings have supported the role of internal simulations of movement in movement planning.…”
Section: 0 Introductionmentioning
confidence: 99%